Da origem no cinema à adaptação do gif: transformações no circuito entre a produção de Pulp fiction e o reconhecimento em confused Travolta - Silva, Flóra Simon da (Universidade do Vale do Rio dos Sinos, 2018)
This dissertation approaches concepts of mediatization in relation to cinema and the appropriations of its elements in digital media by social actors. For this, we propose to analyze the circulation of the Confused Travolta gif, verifying the transformations that occur in the circuit that is formed between its production and recognition. Aims to understand how the appropriations of cinematographic elements such as the cinema logic and the Vincent Vega character produce meaning, create complex circuits of communication, transform social interactions and potentiate new communication devices. In this sense, the question that is raised and that guides research is what transforms, in the circuit of mediatization, when images are constructed from cinematographic elements and are moved to systems of logics different from their original? From a theoretical base, we problematize perspectives of the society of the means for the society in the process of mediatization. Besides that by raising the essential aspects of concepts of circulation and circuits, we develop questions from appropriations and uses in digital media.This theoretical survey articulated, along with some theories of cinema, the possibility of reflection on the cinematographic structure between the assembly and juxtaposition of scenes, production logics and archetypal characters and how these logics are observed in the Confused Travolta gif. Through the analysis it was possible to verify the crossings of mediatization in social practices and, consequently, in the appropriations of the cinematographic elements.We consider that the gif in question, crossed by the logic of mediatization, where social actors produce materials to put into circulation, approaches and distances itself from its original reference, transforms interactions between social actors, produces the agency of flows and conversations in the digital media, resigns the sense of the character Vincent Vega and proposes the formation of a new tentative device of communication through the Confused Travolta gif.
Keywords: Midiatização; Circulação; Imagem; Pulp Fiction; Gif confused travolta; Midiatization; Circulation; Image; Pulp fiction; Confused travolta gif.; ACCNPQ::Ciências Sociais Aplicadas::Comunicação